(untitled) (Journal of actual problems of jurisprudence, 2019)
In article problem questions of legal proceedings on cases of bankruptcy, their place in a civil procedural law of the Republic of Kazakhstan regarding a ratio of bankruptcy of individual entrepreneurs and the legal entities, the accelerated rehabilitation and rehabilitation of legal entities to a special type of production are considered. Also in article legal proceedings questions on cases of bankruptcy on the basis of achievements of science of a civil procedural law are considered. Key words: bankruptcy, insolvency, bankruptcy of individual entrepreneurs and legal entities.